An in vivo study: prebiotic evaluation of the resistant starch from Metroxylon sagu on obesity using fat-induced rats - Thompson, Mayrilyn Solo; Hui Yan, Tan; Mikal, Kathleen Michelle; Shamsudin, Shafarin Mohammad; Rashed, Aswir; Sarbini, Shahrul Razid (Elsevier, 2023)
One hypothesis that has gained attention for the occurrence of obesity is due to the reaction of the microorganisms in our gut. It has been established that the food intake and dietary composition modulates the composition of the gut microbiota. The main aim for the study is to determine the potential of sago starch as prebiotic. Whereby, sago starch is one of the major commodities in East Malaysia, that derived from sago palm tree and contains high resistant starch. This study also evaluates the range for low dosage of resistant starch from sago starch that can confers health benefit on the fat-induced rats for its functional value. The Sprague Dawley rats was fat-induced prior to resistant starch intervention. Fecal samples were collected every two weeks. Short-chain fatty acids production was analyzed using high performance liquid chromatography, and gut microbiota quantification using fluorescent in-situ hybridization method. The finding showed that Bifidobacterium spp. and Lactobacillus spp. showed significant increment (P<0.05) when supplement with sago starch. Short chain fatty acids such as acetate, propionate and butyrate showed increment trends, however not significant. Thus, the study demonstrated that sago starch has similar effect with the commercially available resistant starch indicating the potential as prebiotic.